2019
DOI: 10.33549/physiolres.934328
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anti-Inflammatory Activity of Fatsiphloginum™ (Fatsia japonica) and a New Purified Triterpene-Rich Extract of Saponins (PS-551) in Experimental Model of Arthritis

Abstract: In this study, two extracts from Fatsia japonica-Fatsiphloginum™ (extract of triterpene glycosides containing 45-50 % of fatsiosides (FS)) and purified triterpene-rich extract of saponins with code name PS-551 (PS) were administered in combination with methotrexate (MTX) and in monotherapy to rats suffering adjuvant arthritis (AA). The anti-inflammatory activities of extracts were evaluated as monotherapies in comparison with untreated AA. PS administered in higher dose showed on day 28 effective decrease of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…However, RB in combination with MTX decreased the IL-17A levels in plasma on days 14 and 21 significantly (Figure 5). Our previous results with fatsiphloginum, especially in combination with MTX, are comparable, with results from this study [41]. The anti-inflammatory activity of robinin could be explained also via its metabolites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, RB in combination with MTX decreased the IL-17A levels in plasma on days 14 and 21 significantly (Figure 5). Our previous results with fatsiphloginum, especially in combination with MTX, are comparable, with results from this study [41]. The anti-inflammatory activity of robinin could be explained also via its metabolites.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier findings suggested that major clinical markers, HPV and body weight gain, are remarkably worsened due to inflammation and were effectively diminished by administration of compounds with anti-oxidative and/or anti-inflammatory properties [38][39][40]. The protective effect of MTX against AA development agrees with previously reported results [23,28,37,40,41] as well as with changes of HPV shown in Figure 3. Combination of RB with MTX did not improve these protective effect of MTX (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
“…The activity of GGT is considered a reliable biochemical merit for inflammation and OS; its increased action in organs such as the spleen and joints is believed to be a good indicator of AA development at the systemic and local level [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This combination has shown better results than M and losartan alone (Refaat et al, 2013). In our previous experiments we focused on combination therapy of M with natural substances and extracts, which has shown significant improvement of several inflammatory markers and biometrical parameters (Tsiklauri et al, 2019(Tsiklauri et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%